#### Answer

none of these

#### Work Step by Step

equation 1, y+2=-3(x-5)
y+2 = -3x+15
y = -3x +13
equation 2, 2y = 6x+11
y=3x + $\frac{11}{2}$
m1=-3 and m2=3
m1$\ne$m2 and m1*m2 $\ne$ -1

Published by
Brooks Cole

ISBN 10:

ISBN 13:

none of these

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.